Varicocele is associated with hypogonadism and impaired erectile function: a prospective comparative study - Ji, B.; Jin, X.‐b. (Andrologia, 2017)
Summary We conducted this prospective comparative study to examine the hypothesis that varicocele was associated with hypogonadism and impaired erectile function as reflected in International Index of Erectile Function‐5 (IIEF‐5) scores as well as nocturnal penile tumescence and rigidity (NPTR) parameters. From December 2014 to December 2015, a total of 130 males with varicocele complaining of infertility or scrotal discomfort and 130 age‐matched healthy males chosen from volunteer healthy hospital staff as controls were recruited in this study. Serum testosterone (TT) levels and IIEF‐5 scores as well as NPTR parameters were evaluated and compared between varicocele and control subjects. All participants were further grouped into hypogonadism based on the cut‐off value 300 ng/dL. A total of 45 of 130 patients were identified as hypogonadism, while it was not found in control subjects. A multivariate logistic regression with likelihood ratio test revealed that TT levels as well as grade III and II varicocele posed significant indicators for hypogonadism occurrence (chi‐square of likelihood ratio = 12.40, df = 3, p < .01). Furthermore, TT levels and infertility duration were associated with IIEF‐5 scores in a multivariate linear regression analysis (adjusted R2 = 0.545). In conclusion, the correlation of grade III and II varicocele with an increased risk of hypogonadism was confirmed in this study and an impaired erectile function correlated with TT levels and infertility duration was also observed.